2016
DOI: 10.1021/acs.biochem.5b01282
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Rev1 C-Terminal Domain and the PolD3 Subunit of Polζ Suggests a Mechanism of Polymerase Exchange upon Rev1/Polζ-Dependent Translesion Synthesis

Abstract: Translesion synthesis (TLS) is a mutagenic branch of cellular DNA damage tolerance that enables bypass replication over DNA lesions carried out by specialized low-fidelity DNA polymerases. The replicative bypass of most types of DNA damage is performed in a two-step process of Rev1/Polζ-dependent TLS. In the first step, a Y-family TLS enzyme, typically Polη, Polι or Polκ, inserts a nucleotide across DNA lesion. In the second step, a four-subunit B-family DNA polymerase Polζ (Rev3/Rev7/PolD2/PolD3 complex) exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 85 publications
1
98
0
Order By: Relevance
“…These studies provide a molecular basis for a deeper insight into the highly complex mechanism mediating regulation and assembly of the TLS machinery. Thus, according to the current understanding, instead of competing for Rev1 binding, implied by the original model (Guo et al , 2003; Ohashi et al , 2004), pol ζ and one of the Y-family TLS polymerases cooperate in lesion bypass by simultaneous binding to the Rev1 scaffold (Kikuchi et al , 2012; Liu et al , 2013; Pozhidaeva et al , 2012; Pustovalova et al , 2012; Pustovalova et al , 2016; Wojtaszek et al , 2012a; Wojtaszek et al , 2012b; Xie et al , 2012; Xing et al , 2009) (Figure 3). This model suggests a mechanism by which Rev1 facilitates polymerase switching that is required to catalyze the two consecutive steps of TLS (Figure 3B & C) without the need for polymerase dissociation: 1) nucleotide insertion opposite the damaged site and 2) extension of the nascent strand past the lesion [for the origins of the two-step TLS model see (Bridges and Woodgate, 1985; Goodman and Woodgate, 2013; Livneh et al , 2010; Prakash and Prakash, 2002)].…”
Section: Tls Protein Interaction Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies provide a molecular basis for a deeper insight into the highly complex mechanism mediating regulation and assembly of the TLS machinery. Thus, according to the current understanding, instead of competing for Rev1 binding, implied by the original model (Guo et al , 2003; Ohashi et al , 2004), pol ζ and one of the Y-family TLS polymerases cooperate in lesion bypass by simultaneous binding to the Rev1 scaffold (Kikuchi et al , 2012; Liu et al , 2013; Pozhidaeva et al , 2012; Pustovalova et al , 2012; Pustovalova et al , 2016; Wojtaszek et al , 2012a; Wojtaszek et al , 2012b; Xie et al , 2012; Xing et al , 2009) (Figure 3). This model suggests a mechanism by which Rev1 facilitates polymerase switching that is required to catalyze the two consecutive steps of TLS (Figure 3B & C) without the need for polymerase dissociation: 1) nucleotide insertion opposite the damaged site and 2) extension of the nascent strand past the lesion [for the origins of the two-step TLS model see (Bridges and Woodgate, 1985; Goodman and Woodgate, 2013; Livneh et al , 2010; Prakash and Prakash, 2002)].…”
Section: Tls Protein Interaction Networkmentioning
confidence: 99%
“…For example, it has been reported that the large region of hREV7 (~130 amino acids) is required for the interaction with the C-terminal domain of hREV1 (Murakumo et al , 2001) and an approximately 100 amino acid region in C-terminal domain of human REV1 (Figure 2A, Protein Interaction Region, PIR) is required for the interaction with all other polymerases from the Y-family, as well as with Rev7 and PolD3 subunits of pol ζ (Figure 2C) (Guo et al , 2003; Masuda et al , 2003; Murakumo et al , 2001; Ohashi et al , 2004; Pustovalova et al , 2016). On the other hand, sequences as short as 16 amino acids in pols η, ι and κ (Figure 2B, one Rev1-interacting region (RIR) in pols ι and κ and two such motifs in pol η) are sufficient for recognition by hRev1 (Figure 2C) (Ohashi et al , 2009).…”
Section: Tls Protein Interaction Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…6,9 In humans, Rev1 PPIs with all other TLS enzymes are mediated by its C-terminal (Rev1-CT) domain that can bind R ev1- i nteracting r egions (RIR) from Polκ, Polη, Polι and PolD3 and, at the same time, interact with the accessory Rev7 subunit of Polζ. 2935 Cells deficient in Rev1 exhibit increased sensitivity to DNA damage and a significantly reduced mutation rate. 3638 Deletion of the Rev1-CT domain confers a similar DNA damage sensitive non-mutable phenotype, suggesting that this domain is critical for the cellular function of the TLS pathway.…”
Section: Introductionmentioning
confidence: 99%